Economic growth of Ukrainian regions and determinants of financial resilience: Modeling the causal nexus - Olha Mulska; Iryna Storonyanska; Khrystyna Patytska; Ulana Ivaniuk; Halyna Voznyak (Problems and Perspectives in Management, 2023)
Stable economic progress and upward dynamics of economic growth in the regions depend on their level of security and ability to withstand adverse macroeconomic and other shocks, as well as the state of affairs in which risks cannot be transformed into threats and dangers. The study aims to assess the causal nexus and the level of sensitivity of regional economic growth components to changes in financial resilience determinants. The research methods include systemic and structural analyses (building an information and analytical model for studying financial resilience), Granger test (identifying causal relationships between the variables under study), risk theory (studying the nature of fluctuations), and spatial and temporal approach. Data from the regions (oblasts) of Ukraine between 2015 and 2021 form the informational and analytical basis of the study. The paper reveals that the targeted use of transfers for socio-economic progress, increasing investment capacity, and bolstering financial and budgetary autonomy through increasing local budget revenues are the dominant financial determinants of regional economic growth. The results show that the most dominant causal nexus exists between (1) budgetary efficiency, interest rates on consumer/mortgage loans, and SME development, (2) the volume of loans/deposits and labor market efficiency and SME development, and (3) innovation development and foreign economic cooperation. Intensification of investment activity is crucial for ensuring real changes in the economic structure of all regions, particularly outsiders, accelerating transformation processes, mitigating regional economic divergence, and increasing competitiveness. AcknowledgmentsThe study was conducted within the framework of the “Financial Determinants of Ensuring Economic Growth of Regions and Territorial Communities based on Behavioral Economics” project (№ 2020.02/0215) funded by the National Research Foundation of Ukraine (Competition “Support for Research of Leading and Young Scientists”).